1996
DOI: 10.1902/jop.1996.67.9.866
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Subgingival Antimicrobial Therapy on the Levels of Stromelysin and Tissue Inhibitor of Metalloproteinases in Gingival Crevicular Fluid

Abstract: Recent investigations imply that a key mechanism in the pathogenesis of periodontal disease may be the ability of oral microorganisms to induce production and/or activation of matrix metalloproteinases (MMPs) in the host tissues. It has been suggested that the pharmacologic inhibition of MMP activity could play an important role in achieving a desirable outcome in periodontal therapy. The efficacy of locally delivered antibiotics on the level of gingival crevicular fluid (GCF) stromelysin (SL) and tissue inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
20
0
4
Order By: Relevance
“…It has been shown that the concentration of TIMP-1 in saliva of periodontitis patients is much lower than that from healthy and edentulous patients [5]. Interestingly, subgingival antimicrobial therapy signi¢cantly increased the level of TIMPs in gingival crevicular £uid [15]. Our study reveals that P. gingivalis can, through the action of cysteine proteinases, inactivate TIMP-1.…”
Section: Resultsmentioning
confidence: 52%
“…It has been shown that the concentration of TIMP-1 in saliva of periodontitis patients is much lower than that from healthy and edentulous patients [5]. Interestingly, subgingival antimicrobial therapy signi¢cantly increased the level of TIMPs in gingival crevicular £uid [15]. Our study reveals that P. gingivalis can, through the action of cysteine proteinases, inactivate TIMP-1.…”
Section: Resultsmentioning
confidence: 52%
“…Kalibrasyon; Periotron için, sıvıların bilinen hacimlerinin (hassas bir şırınga ile kağıt şeritlere uygulanmasıyla) alete okutulup tanıtılması, bu işlem sonucunda bir kalibrasyon eğrisinin oluş-turulması ve bu kalibrasyon eğrisi yardımıyla da DOS hacminin (Periotron ünitesi (PÜ) veya mikrolitre (μl) cinsinden) belirlenmesidir. 73,74 Kalibrasyon DOS hacmi ölçümlerinde kritik bir aşamadır. Bu aşamadaki eksikler veya hatalar küçük hacimlerde yüzde olarak ciddi ölçüm farklılıklarına ve hatalara neden olur.…”
Section: Kâğıt şErit Yönteminde Dos Hacminin Belirlenmesiunclassified
“…30 DOS örnek alımını kolaylaştırmak amacıyla bukkal, mezyal ve anterior alanların lingual, distal ve posterior alanlara üstün tutulduğu görülmektedir. 74 Değerlendirmeleri etkileyecek bir kontaminasyon türü de, Periotron cihazında DOS örnekleri-nin okutulması sonrasında cihaz kutuplarında meydana gelen kontaminasyondur. Tözüm ve ark.…”
Section: Kâğıt şErit Yönteminde Dos Hacminin Belirlenmesiunclassified
See 2 more Smart Citations